1999
DOI: 10.1530/eje.0.1400583
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of matrix-metalloproteinase-1 and tissue inhibitor of metalloproteinase-1 gene expression in rats by the preovulatory prolactin peak

Abstract: Since structural luteolysis involves deterioration of tissue, the gene expression of matrix-metalloproteinase-1 (MMP-1) and the respective tissue inhibitor of this metalloprotease (TIMP-1) were measured at various times on the day of pro-oestrus and in animals in which the preovulatory prolactin surge was blocked for the duration of 3 cycles by bromocriptine. An additional group of prolactin-blocked rats received a prolactin replacement injection on the afternoon of pro-oestrus. In spontaneously pro-oestrous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In rats, ovulation is also preceded by a Prl surge and the onset of this surge usually precedes the onset of the preovulatory LH surge by 2-4 h (Wuttke & Meites 1970, Butcher et al 1974, Hirsch et al 1993. The preovulatory Prl surge in rats has luteotrophic and luteolytic effects in that it causes augmentation of LH-induced luteinisation and associated increased P 4 secretion (Butcher et al 1972, Döhler & Wuttke 1974, Morishige & Rothchild 1974, as well as regression of old CLs (Malven & Sawyer 1966, Wuttke & Meites 1971) through stimulation of collagenases (Hirsch et al 1999). Blockage of the preovulatory Prl surge by dopaminergic agents in rats did not disturb oestrus cyclicity and ovulation (Döhler & Wuttke 1974), but did result in the accumulation of non-steroidogenic CLs (Wuttke & Meites 1971, Dö hler & Wuttke 1974.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, ovulation is also preceded by a Prl surge and the onset of this surge usually precedes the onset of the preovulatory LH surge by 2-4 h (Wuttke & Meites 1970, Butcher et al 1974, Hirsch et al 1993. The preovulatory Prl surge in rats has luteotrophic and luteolytic effects in that it causes augmentation of LH-induced luteinisation and associated increased P 4 secretion (Butcher et al 1972, Döhler & Wuttke 1974, Morishige & Rothchild 1974, as well as regression of old CLs (Malven & Sawyer 1966, Wuttke & Meites 1971) through stimulation of collagenases (Hirsch et al 1999). Blockage of the preovulatory Prl surge by dopaminergic agents in rats did not disturb oestrus cyclicity and ovulation (Döhler & Wuttke 1974), but did result in the accumulation of non-steroidogenic CLs (Wuttke & Meites 1971, Dö hler & Wuttke 1974.…”
Section: Discussionmentioning
confidence: 99%
“…PRL also alters calcium transport across the plasma membrane [28,29] and has been shown to affect protein synthesis via a calciumdependent system in the corpus luteum [30]. Additional destruction of tissue, in this case extracellular matrix, may be carried out via matrix metalloproteinases, which have been reported to increase in the corpus luteum following PRL treatment to induce luteal regression [31,32], and to be associated with a depletion of protein from the tissue [31].…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin is reported to regulate protein synthesis in animal salivary glands (Sabbadini and Berczi, 1995). In addition, several investigators have reported that prolactin may induce the overexpression of proteinases in the synovial cells of patients with rheumatoid arthritis (Nagafuchi et al, 1999) or during preovulatory peaks (Goto et al, 1999;Hirsch et al, 1999), ie, in a strong prolactin environment. Lastly, Azuma et al (1997) have reported an excessive metalloproteinase-2 production by human salivary gland acinar cells in response to cytokines.…”
Section: Steinfeld Et Almentioning
confidence: 99%